Body fat distribution and its associated factors in Korean women with polycystic ovary syndrome. Issue 10 (9th August 2015) - Jin, Chan Hee; Yuk, Jin Sung; Choi, Kyung Mook; Yi, Kyung Wook; Kim, Tak; Hur, Jun Young; Shin, Jung‐Ho
Abstract Aim To investigate the body fat distribution in Korean women with polycystic ovary syndrome (PCOS) and the association of those distribution with metabolic parameters and hormone profiles. Methods A total 90 patients with PCOS and 97 women without PCOS (control group) were included in this study. Total body fat, abdominal visceral fat, and subcutaneous fat were determined on abdominal fat computed tomography. Lipid profiles and sex‐hormone binding globulin (SHBG), testosterone, free androgen index (FAI), and cortisol were measured in PCOS group. Results Total body fat and body fat distribution in the PCOS group were not significantly different from the control group in Korean women (P = 0.054, P = 0.761, P = 0.104), but abdominal visceral to subcutaneous fat ratio was larger in the PCOS group than the control group (P = 0.047). Not only total body fat and visceral fat, but also subcutaneous fat in the PCOS group had a positive correlation with homeostatic model assessment–insulin resistance, fasting blood sugar, low‐density lipoprotein cholesterol, triglyceride, systolic blood pressure, diastolic blood pressure, fasting insulin, free testosterone, FAI, body mass index, but negative correlation with SHBG and high‐density lipoprotein cholesterol. Conclusions Korean PCOS women had the same body fat distribution as the control group. Subcutaneous fat was also correlated with metabolic parameters and hormone profiles in the Korean PCOS group.